Efficient gaseous thermal insulation aerogels from 2-dimension nitrogen-doped graphene sheets. (June 2017) - Yue, Chenwu; Feng, Jian; Feng, Junzong; Jiang, Yonggang
Graphical abstract: Highlights: A new strategy to restrain the gaseous thermal conductivity was presented. The gaseous thermal conductivity of NDGA was detailedly studied. Aerogels from sheets restrain the gaseous thermal conductivity more efficiently. Aerogels from sheets may be the next generation of thermal insulation materials. Abstract: Gaseous thermal conductivity takes up a great proportion of the thermal conductivity of aerogels. In this work, we present a new strategy to restrain the gaseous thermal conductivity, using 3-dimension nanoporous aerogels from 2-dimension sheets. Experimental results show that the N-doped graphene aerogels, typical nanoporous aerogels from 2-dimension sheets, exhibit very low gaseous thermal conductivity (12.58 mW m −1 K −1 at room temperature) at extremely low bulk density (0.0320 g cm −3 ), suggesting that the nanoporous aerogels from 2-dimension sheets can restrain the gaseous thermal conductivity more efficiently than that from 0-dimension pearls. This finding may significantly contribute to the next generation of thermal insulation materials with lower thermal conductivity and much lower density.